Análise da magia talismânica no islamismo medieval a partir do Grimório Picatrix - Silva, José Ricardo Claudino da (2021)
The present study is situated within the discussions on Islamism and its characteristics in the fields of historiography and cross-culturalism in the Middle Ages. Our research has sought to discuss both talismanic and astrologic confluences in the opus Picatrix, in regards to the construction of medieval grimoires in this period of history. In such context, around 1256, Alfonse X, the wise, king of Castela, had ordered the translation of Ghāyat al-Ḥakīm from Arabic to Latin and Spanish. It is also known that there was a direct translation of this work from Arabic to Latin made still during the 13th century, but which was lost and only a few fragments remained, later found during the 14th century. This opus, known in Western Europe as Picatrix, contains a series of themes involving hermetics, alchemy, esotericism and the magic from the talismans and the planets, going from the 13th to the 18th century. During the 20th century, the German scholar Wilhelm Printz discovered the original work in Arabic (Ghāyat al-Ḥakīm), which translates as “The aim of the Wise” or “The Wise’s goal”. In this sense, it registered the Muslim expansion from the North of Africa, when they conquered a vast region of the Iberian Peninsula (Andaluzia), corresponding to the territories of Gibraltar, Spain, Portugal and part of France, from around the 8th to the 15th century, culminating in the fall of the city of Granada. This moment made it possible to discuss religion and religiosities in Islam and the magic present in Islamism, especially the one involving talismans and amulets, like demonstrated in Picatrix. Besides, there is a series of archaeological findings from the region of Andaluzia shedding light on the matter. The present research is of qualitative and bibliographic nature, approaching this systematic production as reproduced in history and which has legitimated the philosophical and astrological knowledge that became fundamental to the 13th century, along with the formation of medieval Islamic religiosities and societies. As such, this qualitative research resides on seeking for interpretations regarding such experiences in the medieval world, including symbols, beliefs and politics and their relation with magic, in a cultural-historical sense. This entanglement provides the sustenance of the diversity and the comprehension of the matter in question. The arguments of specialists like Silveira (2016), Samsó (1992), Roza Candás (2014), Medina (2014), Mattos (2001), Cravioto (2005), were brought into light, besides a few others. At the end of our exploration, it is possible to assert the relevance of this religiosity in the field of Religious Studies, going through its epistemological trajectory and some of its problems along history, when proposing concepts and definitions regarding religion. In what concerns Islamic medieval magic, it is going to be of utter importance to situate it in a perspective of the Empirical Science of Religion, a branch of knowledge coming from the Religious Studies, in an attempt to bring it to an academic debate.